Risk factors in household contacts of leprosy patients in northern Brazil (Research, Society and Development, 2020)
The evaluation and examination of household contacts of leprosy patients is an important factor in breaking the epidemiological chain of transmission. This study aims to identify risk factors for the development of leprosy among household contacts of leprosy cases living in a peripheral area in the city of Belém-PA. This is a prospective, descriptive and cross-sectional study with a quantitative approach, which 2017 to 2018, intra-household contacts of leprosy patients seen at a health unit from 2016 to 2017. Dermatoneurological examinations and blood collection was performed to perform anti-PGL-I serology. 96 household contacts from 39 index cases were analyzed, of which the majority are female (65.62%), aged 31 to 50 years (37.49%), and only elementary school (54.17%). Conditions such as living with contaminating forms, housing with little healthiness and low schooling are present in the studied group and are at risk for illness from leprosy.